The Law on sales, agency and credit transactions - De Leon, Hector S. (Manila, Philippines : Rex Book Store, 2005)
The book already contains numerous examples not only to assist the student in the proper interpretation of the law but also to train him/her in the practical application of legal provisions in specific circumstances.
Preface -- Sales Nature and Form of the Contract -- Capacity to Buy or Sell -- Effects of the Contract When the Thing Sold Has Been Lost -- Obligations of the Vendor -- Obligations of the Vendee -- Actions for Breach of Contract of Sale of Goods -- Extinguishment of Sale -- Assignment of Credits and Other Incorporeal Rights -- General Provisions -- Barter or Exchange -- The Bulk Sales Law -- Agency Nature, Form and Kinds of Agency -- Obligations of the Agent -- Obligations of the Principal 313 Credit Transactions -- A Loan -- Simple Loan or Mutuum -- Deposit Deposit in General and Its Different Kinds -- Voluntary Deposit -- Necessary Deposit -- Sequestration or Judicial Deposit -- Guaranty Nature and Extent of Guaranty -- Effects of Guaranty -- Extinguishment of Guaranty -- Legal and Judicial Bonds -- Pledge Provisions Common to Pledge and Mortgage -- Provisions Applicable Only to Pledge -- Real Mortgage -- Antichresis -- Chattel Mortgage -- Answers to Study Guide.
Keywords: SALES -- LAW -- PHILIPPINES